ChemInform Abstract: Lipase‐Catalyzed Knoevenagel Condensation Between α, β‐Unsaturated Aldehydes and Active Methylene Compounds. Issue 43 (21st October 2014) - Wang, Zhi; Wang, Chun‐Yu; Wang, Hao‐Ran; Zhang, Hong; Su, Ya‐Lun; Ji, Teng‐Fei; Wang, Lei
Abstract Optimum reaction conditions (type of lipase, solvent, water content in the reaction mixture) are examined for the lipase‐catalyzed title reaction.